UJI SENYAWA ANTIMIKROBA DARI ASAM LEMAK DAN FATTY ACID METHYL ESTER (FAME) MIKROALGA Nannochloropsis oculata - Zulkarnain Chaidir; Sari Rahmi; Marniati Salim (Prosiding Seminar Nasional Pakar, 2019)
Microalgae contains many bioactive molecules including lipid that can be useful for development of antimicrobial compounds. The aim of this research is to test antimicrobial compounds from fatty acid and fatty acid methyl ester (FAME)from microalgae Nannochloropsis oculata. Lipid from microalgae was extracted using hexane and transesterfied using methanol dan sulfuric acid p.a as catalist. Antimicrobial activities were tested using disc diffusion methode against Staphylococcus aureus, Escherichia coli, and yeast Candida albicans, at varying concentrations are 100, 200, and 300 mg/L. The result shown that fatty acids and FAME from microalgae Nannochloropsis oculata have antibacterial activity and do not have anti-candidal activity against Candida albicans. Antibacterial activity of fatty acids is higher than antibacterial activity of FAME on both bacteria. The result shown that fatty acids and FAME contained in lipid of microalgae Nannochloropsis oculata are palmitic acid, stearic acid, methyl lauric, and methyl stearic.